ALZ‐NET: Using Real World Evidence to Inform the Future of Alzheimer's Treatment and Care. (20th December 2022) - Rabinovici, Gil D.; Rafii, Michael S; Apgar, Charles; An, Na; Barakos, Jerome; Brangman, Sharon A; Daffner, Kirk R; Edelmayer, Rebecca M.; Gatsonis, Constantine; Hakim, Rosemarie; Hanna, Lucy; Jicha, Gregory A; et al.
Abstract: Background: There are over 100 therapies being tested in clinical trials for Alzheimer's disease (AD) today. With therapies undergoing regulatory review and a growing DRUG DEVELOPMENT pipeline, the field is entering a new era of molecular‐specific therapies. A national registry represents an opportunity to evaluate the longitudinal outcomes of patients treated with any novel FDA‐approved AD therapy in real‐world settings, to inform clinical practice. Method: The Alzheimer's Association, the American College of Radiology, the American Society of Neuroradiology, the Department of Biostatistics, Brown University School of Public Health and the Critical Path Institute, along with other clinical research and imaging experts, are launching Alzheimer's Network for Treatment and Diagnostics (ALZ‐NET). ALZ‐NET will build on expertise from successful registries in other therapeutic areas and the IDEAS and New IDEAS studies which demonstrated large‐scale, real‐world data collection in dementia practice is feasible for addressing critical research questions. Networks of dementia practices and imaging facilities will provide the foundation of ALZ‐NET. Data collection and sharing will be fully compliant with human participant protections, privacy and patient/provider autonomy. Result: ALZ‐NET will collect longitudinal clinical and safety data for enrolled patients treated with novel FDA‐approved AD therapies and will track patient long‐term health outcomes (effectiveness and safety), associated with use in real‐world settings. ALZ‐NET aims to assess clinical course of people from a variety of backgrounds and communities, to achieve representativeness beyond the populations historically enrolled in clinical trials. Objectives of ALZ‐NET: Develop multisite network for enrolling providers and collection of patient data. Collect baseline and longitudinal patient data, including measures of cognition, function, and long‐term safety. Track health outcomes and resource utilization through existing databases. Collect and archive diagnostic and safety data and neuroimaging, genetic and fluid biomarkers. Share deidentified data, images and biosamples with research community and other stakeholders. Conclusion: ALZ‐NET will establish a network of sites with an expandable platform, allowing for the collection of real‐world data from enrolled patients receiving novel FDA‐approved AD therapies. ALZ‐NET will be a resource for evidence gathering, information sharing, and education across clinical and research communities, encouraging innovative, inclusive research and supporting opportunities to improve care.